2012
DOI: 10.1098/rsif.2011.0715
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnetically simulated zero-gravity and enhanced gravity on the walk of the common fruitfly

Abstract: Understanding the effects of gravity on biological organisms is vital to the success of future space missions. Previous studies in Earth orbit have shown that the common fruitfly (Drosophila melanogaster) walks more quickly and more frequently in microgravity, compared with its motion on Earth. However, flight preparation procedures and forces endured on launch made it difficult to implement on the Earth's surface a control that exposed flies to the same sequence of major physical and environmental changes. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 45 publications
4
17
0
1
Order By: Relevance
“…Note the differences between the two genders in over-expression (red areas) and that, for one gender, the over-expressed areas correspond to downregulated areas for the other gender. This opposite effect for males and females, which has been observed previously in our complementary experiments [18], can also be seen in lessexpressed areas of the image. This suggests a global effect in …”
Section: The Effect Of Mechanical Simulators On Gene Expression Depensupporting
confidence: 60%
See 3 more Smart Citations
“…Note the differences between the two genders in over-expression (red areas) and that, for one gender, the over-expressed areas correspond to downregulated areas for the other gender. This opposite effect for males and females, which has been observed previously in our complementary experiments [18], can also be seen in lessexpressed areas of the image. This suggests a global effect in …”
Section: The Effect Of Mechanical Simulators On Gene Expression Depensupporting
confidence: 60%
“…It is established that Drosophila imagoes exhibit a marked enhancement in motility when they are exposed to altered gravity conditions, due in part to their misorientation relative to the gravity vector [18,22,23]. Recent work has shown that differences in the age and gender of the imagoes can influence the degree of responsiveness to altered gravity, and suggested that altered motility can have a consequence by reducing mating/sexual behaviour and increasing energy metabolism and aging [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of changes in gravity on living organisms have mainly been studied by performing complex, expensive experiments on Earth and in space (Ishay and Sadeh, 1975;Hill et al, 2012;Herranz et al, 2013). In view of the heavy investments required to perform experiments on insects on these lines, we decided to develop a lowcost platform.…”
Section: Introductionmentioning
confidence: 99%